Edukasi Pentingnya Pemahaman Hukum tentang Kesehatan Anak dalam Mencegah Stunting di Dusun Nggaron - Lestari, Retnaning Muji; Sasanti, Serafina Damar; Utaminingtyas, Farida; Nurfieni, Amrin (Universitas Pahlawan Tuanku Tambusai, 2025)
Stunting is a chronic nutritional problem caused by prolonged undernutrition and repeated infections. The Indonesian government has updated its health law policy through Law No. 17 of 2023 on Health, which guarantees children's rights to nutrition and basic health services. Article 126 states that “children have the right to basic health services that include nutrition, immunization, monitoring of children's growth and development, and protection from disease”. Therefore, it is important to provide education on legal understanding of child health to have an impact on mothers' preventive attitudes in preventing stunting. This education is expected to contribute to accelerating the reduction of stunting rates. The purpose of this activity is to provide a legal understanding of child health and preventive steps for mothers in preventing stunting. Methods This activity was carried out by delivering material then continued with discussion and question and answer sessions. Based on the evaluation results, all participants were declared successful in understanding the material. The expected results are the formation of preventive attitudes of mothers in preventing stunting.